Peningkatan Efisiensi Manajemen Aset Melalui Pendekatan Inovatif Dan Teknologi Terkini - Fakhri Miftah Firdaus; Denara Akmal; Ikin Ainul Yakin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Asset management is a key aspect in maintaining organizational competitiveness in an era of continuously developing business. This research aims to investigate how innovative approaches and the use of the latest technology can improve asset management efficiency in various organizational contexts. The research method used is a qualitative approach, with data collection through analysis of documents and related literature. The research results reveal that innovative approaches to asset management involve changes in organizational culture, including greater awareness of asset value and improved interunit collaboration. Recent technologies, such as the Internet of Things (IoT) and Big Data Analytics, have enabled real-time monitoring and analysis of assets, leading to faster and more accurate decision making. This research provides a deeper understanding of how innovative approaches and the latest technology can change the paradigm in asset management. The practical implication of this research is that organizations should invest in the latest innovations and technologies to achieve better efficiency in their asset management. These findings can also provide guidance for organizational leaders in designing more effective asset management strategies in the digital era.